Theoretical Evaluations of Probability of Photons Yield Depending on Quantum Chromodynamics Theory - Al-Agealy, Hadi J M; Sahib, Mudhafar J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Aim of this research is the description with evaluation the photons rate probability at quark-gluon reactions processes theoretically depending on quantum color theory. In high energy physics as well as quantum field theory and quantum chromodynamics theory,they are very important for physical processes. In quark–gluon interaction there are many processes, the Compton scattering, annihilation pairs and quark–gluon plasma. There are many quantum features, each of three and systems that taken which could make a quark–gluon plasma in character system. First, electric quark charge and color quantum charge that’s satisfied by quantum number. Second, the critical temperature and photon energy. Moreover, for such three systems have variety quantum flavor numbers: 2, 3 and 4, the photons rate are evaluated at system energy limited with critical temperature: 144 MeV. However, due to the quark–gluon plasma producing in heavy ions collisions, the photons rate is increasing with decreasing of coupling constant and photons energy in quark-quark interaction systems.